Manipulating Immune Tolerance with Micro-RNA Regulated Gene Therapy - Goudy, Kevin S.; Annoni, Andrea; Naldini, Luigi; Roncarolo, Maria Grazia (Frontiers in Microbiology, 2011)
The successful use of in vivo gene therapy depends upon controlling the immune response to the therapeutic transgene to allow stable, long-term transgene expression. Over the last decade several vector-based and pharmacological approaches to control the immune-mediated clearance of transgene expressing cells after viral delivery have been explored. One important outcome from these studies is the concept that expression of transgene in tolerance-promoting organs, such as the liver and tolerogenic antigen presenting cells, can help safeguard transgene expressing cells from immune-mediated clearance. With this in mind, gene therapists are specifically targeting these avenues by manipulating their vectors in three main areas: i) incorporating tissue/cell specific promoters, ii) viral-capsid engineering to alter tropism and avoid pre-existing immunity, and iii) including micro-RNA (miR) targets into expression cassettes. The combination of these three layers of vector regulation greatly enhances the targeting of “tolerogenic cells” and limits the off-target expression of the transgene, which can lead to the induction of transgene-specific pathogenic effector T cells. In this review, we discuss the application of using miR transgene regulation to generate tolerogenic responses and speculate on possible mechanisms used by the liver to induce the transgene specific regulatory T cells.